DNA methylation patterns in umbilical cord blood from infants of methadone maintained opioid dependent mothers - Adegboyega, Oluwatobi; Gayen nee’ Betal, Suhita; Urday, Pedro; Huang, Rachel; Bodycot, Katherine; Al-Kouatly, Huda B.; Solarin, Kolawole; Chan, Joanna S. Y.; Addya, Sankar; Boelig, Rupsa C.; Aghai, Zubair H. (Scientific reports, 2024)
Methadone maintenance treatment for opioid dependent mothers is standard of care. Infants of methadone maintained opioid dependent (MMOD) mothers have better outcomes compared to infants of opioid dependent mothers without treatment. However, when compared to non-exposed infants, infants of MMOD mothers are associated with worse outcomes. We conducted a pilot study to examine genome wide differential DNA methylation using cord blood samples from sixteen term and near-term infants of MMOD and opioid naïve mothers, excluding Infants with chorioamnionitis. A total of 152 differentially methylated loci were identified at a difference >  + 2, < − 2 and p-value < 0.05. There were 90 hypermethylated loci (59 annotated genes) and 62 hypomethylated loci (38 annotated genes) observed. The hypermethylated and hypomethylated DNA changes involved multiple genes, pathways and networks that may explain some of the changes seen in infants of MMOD mothers. Top hypermethylated and hypomethylated genes involved areas of cell growth, neurodevelopment, vision and xenobiotic metabolism functions. Our data may explain the role of key pathways and genes relevant to neonatal outcomes seen from methadone exposure in pregnancy. Functional studies on the identified pathways and genes could lead to improved understanding of the mechanisms and identify areas for intervention.